2020
DOI: 10.1155/2020/9184284
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Nanocarrier-Based Targeted Chemotherapy: Selective Delivery of Anticancer Drugs for Effective Lung, Colon, Cervical, and Breast Cancer Treatment

Abstract: Chemotherapy drugs are cytotoxic to tumor cells, but their lack of specificity leads to a range of side effects. The off-target effects of such drugs can be improved through the use of nanoparticles (NPs). Administered NPs show enhanced accumulation in tumor tissue near the blood vessels, enhancing both anticancer drug permeability and tumor retention. Several nanocarriers are now approved for clinical use in a range of cancer therapies, and many novel formulations are in the later stages of clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 128 publications
0
22
0
Order By: Relevance
“…Small nanocarriers with those tumor properties are believed to be suited for passive targeting of anticancer drugs, at relatively smaller dimensions than abnormal blood-vessel gaps, and can easily reach and selectively localize tumors. 22 However, recent studies have demonstrated that interendothelial gaps on tumors are not responsible for NP transport and accumulation into solid tumors. One study found that active processes take place for up to 97% of NP transport into tumors through endothelial cells.…”
Section: Types Of Targeted Drug-delivery Systemsmentioning
confidence: 99%
“…Small nanocarriers with those tumor properties are believed to be suited for passive targeting of anticancer drugs, at relatively smaller dimensions than abnormal blood-vessel gaps, and can easily reach and selectively localize tumors. 22 However, recent studies have demonstrated that interendothelial gaps on tumors are not responsible for NP transport and accumulation into solid tumors. One study found that active processes take place for up to 97% of NP transport into tumors through endothelial cells.…”
Section: Types Of Targeted Drug-delivery Systemsmentioning
confidence: 99%
“…But same as lipid-based nanomaterials, there are still many restrictions waiting to be overcome. Ideally, safe 6 Journal of Nanomaterials nanomaterials that could be loaded with various drugs and be able to target the specific cells in the brain remotely are highly expected.…”
Section: Nanomaterials For Drug Delivery Across the Blood-brainmentioning
confidence: 99%
“…In addition, specially designed nanomaterials can also improve the thrombolytic process of ischemic stroke and the effect of stem cell transplantation. Similarly, in cancer treatment, nanomaterials rely on their unique advantages to accurately target some biotoxic drugs to cancer tissues without causing damage to normal tissues [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticle based drug delivery systems are being extensively implemented in conventional approaches and combinational therapies of cancer treatment. These nanocarriers have shown improved efficacy, selectivity, stability, bio distribution, biocompatibility, and pharmacokinetics of anti-cancer drugs while overcoming the issues of multiple drug resistance and toxicity [ 13 , 14 ]. A variety of payloads, e.g., imaging agents, antibodies, photosensitizers, nucleic acids, and anti-cancer drugs can be loaded into these nanocarriers making them a versatile platform.…”
Section: Introductionmentioning
confidence: 99%